Penerapan Petunjuk Teknis Operasional ( PTO ) Pada Kegiatan Tridaya LKM Bakti Mandiri Samarinda - -, Fittono - (EKONOMIA, 2014)
LKM Bakti Mandiri is an institution led collegial collective, autonomous, independent, initiated and formed directly by the residents in the village Handil Bakti, with the aim to empower the community, under the auspices of the PNPM Mandiri. Each MFI pelaksananaan Tridayanya Bakti Mandiri activities set forth in the Technical Operational Guidelines, the National Program for Community Empowerment (PNPM), as contained in the circular issued by the Ministry of Interior, represented by the Director General of Community No. 414.2 / 3717 / PMD in 2008.Formulation of the problem in this study is